Subtypes and phylogenetic analysis of human immunodeficiency virus-1 in Jayapura - Mirna Widiyanti; Tri Wibawa; Holy Arif Wibowo (Universa Medicina, 2014)
BACKGROUND Human immunodeficiency virus (HIV) is a retrovirus that infects human immune system. HIV is genetically differentiated into HIV-1 and HIV-2. HIV- 1 is classified into 3 groups : M,N and O. M Group is divided into 9 subtypes, namely : A, B, C, D, F, G, H, J and K. HIV subtype mapping would become a good reference to study the epidemiology of HIV-1. HIV phylogenetic analysis required to understand virus origin, geographical distribution and tracking parameter of HIV transmission process in sample area. The objective of this study was to determine HIV-1 subtype distribution and the relationship between HIV-1 subtypes from with genBank HIV isolate based on envelope gene fragment. METHODS A cross setional design was conducted involving 36 subjects in Jayapura between January to March 2013. Blood samples were taken and analyzed using reverse transcription polymerase chain reaction (RT-PCR), nested PCR and confirmed with sequencing. Phylogenetic analysis performed along 400 bp of envelope gene fragment. The data were analyzed with Bioedit ver.7 and MEGA 5.1. software. RESULT Two types of HIV-1 subtype were found in Jayapura Regency. CRF01_AE was confirmed in 31 patients (86.1%) and subtype B in 5 patients (13.9%). Phylogenetic analysis showed phylogenetic relationship between CRF01_AE from jayapura with subtype from Singapore and Thailand, while subtype B from Jayapura were closely related with subtype from United States and United Kingdom CONCLUSION This study reflect the independent introduction of multiple HIV-1 strains into Papua, with the rapid spread in the majority of infected patients tested of single strain of HIV-1 (CRF01_AE).